OPERATIONAL PERFORMANCE OF THE BRONDONG FISHING PORT LAMONGAN REGENCY OF EAST JAVA PROVINCE - Diana Putri Pertiwi; Syaifuddin Syaifuddin; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis survey activity was conducted on January – February 2018 at Brondong Fishing Port Brondong district or Lamongan regency . This study aims to determine the activities and facilities that support the operations in Brondong Fishing Port. The results showed that the activities and facilities in Brondong Fishing port are very supportive of operational performance in Brondong Fishing Port. The existing facilities in there namely: Dock, harbor pool, breakwaters, plaster, road complex area, drainase, ice factory, clean water tank, shop and mosque While the activities contained in fishing port is mooring labyrinth, charging supplies such as charging fresh water, fuel (BBM), and foodstuffs, fish landing activities, as well as marketing activities of catches such as auctions and exports. Keywords:Brondong Fishing Port, Facilities, Activities and Operational.